Ectoparasite infection of two commercially important fish species in the Negombo Estuary, Sri Lanka: Flathead grey mullet (Mugil cephalus) and Green chromide (Etroplus suratensis) - Epa, Udaya Priyantha Kankanamge; Dayananda, M.G.G.P. (Department of Aquaculture, 2025)
This study aimed to assess the prevalence, diversity, and intensity of external parasitic infections in Mugil cephalus and Etroplus suratensis from the Negombo estuary, Sri Lanka, and to evaluate their potential impact on fish health and condition factors. External parasites were identified in 210 M. Cephalus and E. Suratensis collected from the Negombo estuary in Sri Lanka. Both fish species had high disease prevalence, with M. Cephalus infected at 86% and E. Suratensis infected at 78%, respectively. Fish parasites belonging to Phylum Apicomplexa, Phylum Protozoa, Phylum Nematoda, Sub Phylum Crustacea (copepods and isopods), and Class Trematoda (monogeneans) were found in both fish species. The mean parasitic intensity was significantly higher in E. Suratensis than in M. Cephalus. Caligus curtus, C. Robustus, Dactylogyrus spp., Ergasilus boleophthalmi, E. Parvitergrum, and Cryptocaryon sp. They were recorded at a higher intensity in both fish species. According to the Shannon-Weiner diversity index, M. Cephalus had a higher parasite diversity (1.37) than E. Suratensis (1.25). Ectoparasites were more common in the gills of M. Cephalus (84.6%) and E. Suratensis (88.5%) than in the skin, fins, and operculum. The condition factor of infected E. Suratensis (1.91±0.82) was slightly lower than that of uninfected fish (2.2±0.76). However, there was no difference in condition factor between infected (1.84±0.41) and uninfected M. Cephalus (1.87±0.61). The number of infected parasites per fish was unrelated to either length class or condition factor in either species (p>0.05). The findings of this study could be used to manage disease outbreaks in the wild and aquaculture development efforts in estuarine environments.